Rhythmic potassium transport regulates the circadian clock in human red blood cells. Issue 1 (December 2017) - Henslee, Erin; Crosby, Priya; Kitcatt, Stephen; Parry, Jack; Bernardini, Andrea; Abdallat, Rula; Braun, Gabriella; Fatoyinbo, Henry; Harrison, Esther; Edgar, Rachel; Hoettges, Kai; Reddy, Akhilesh; et al.
Abstract Circadian rhythms organize many aspects of cell biology and physiology to a daily temporal program that depends on clock gene expression cycles in most mammalian cell types. However, circadian rhythms are also observed in isolated mammalian red blood cells (RBCs), which lack nuclei, suggesting the existence of post-translational cellular clock mechanisms in these cells. Here we show using electrophysiological and pharmacological approaches that human RBCs display circadian regulation of membrane conductance and cytoplasmic conductivity that depends on the cycling of cytoplasmic K+ levels. Using pharmacological intervention and ion replacement, we show that inhibition of K+ transport abolishes RBC electrophysiological rhythms. Our results suggest that in the absence of conventional transcription cycles, RBCs maintain a circadian rhythm in membrane electrophysiology through dynamic regulation of K+ transport. Circadian rhythms usually rely on cyclic variations in gene expression. Red blood cells, however, display circadian rhythms while being devoid of nuclear DNA. Here, Henslee and colleagues show that circadian rhythms in isolated human red blood cells are dependent on rhythmic transport of K+ ions.